PERAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Setiawati, Nanda Ayu; Pangaribuan, Yetti Rosmawati; Limbong, Winny Sunfrsika; Sutarna, Trinanda (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2023)
The purpose of this study was to find out how the role of parents on the learning motivation of fifth grade students at SDN 060960 Belawan. This type of research is a qualitative approach with data analysis techniques according to Miles and Huberman. The activities in this data analysis are data reduction, data display and conclusion drawing/verification. The subjects and objects of this data are parents and students of class V SDN 060960 Belawan totaling 26 people consisting of mothers, fathers and students who will be studied using observation, interviews and documentation. Based on the results of research that has been done through interviews, observations and documentation that the role of parents on student learning motivation is giving attention, giving rewards and appreciation in the form of praise and providing learning facilities. It was found that the role of parents on students' learning motivation was not sufficient to carry out its role on student learning motivation, such as: Not paying attention to children, Not providing books and learning facilities for children. It can be concluded that the role of parents on the learning motivation of fifth grade students at SDN 060960 Belawan is not all done well, because there are some parents who are still unable to carry out their role in motivating children's learning, this is evidenced by the results of interviews between researchers and parents of students.